The Effect Of Service and Trust on Muzakki satisfaction at Baitul Mal, Aceh Tamiang Regency - Deni Riani deni; Lili Apriliani (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Purpose – This study aims to determine whether service and trust affect the satisfaction of muzakki at Baitul Mal, Aceh Tamiang Regency, either partially or simultaneously. Method – In this study, the data used are primary and secondary data using questionnaire, interview, and observation methods. The technique used for sampling in this study is purposive sampling, which is done by taking people who are properly selected by the researcher according to the specific characteristics possessed by the sample. Based on the random conducted, the researchers took a sample in Kuala Simpang District. Then the data analysis techniques used in this research are validity test, reliability test, classical assumption test and multiple regression analysis. Research Results - The results of this study obtained the effect of service on muzakki satisfaction at Baitul Mal showing a t value of 4.183 with a sig value of 0.000 <0.05, this means that service partially has a significant positive effect on muzakki satisfaction at Baitul Mal, Aceh Tamiang Regency. The effect of trust on muzakki satisfaction at Baitul Mal shows a t - count value of 2.421 with a sig value of 0.017 > 0.05, then partially trust has a positive and insignificant effect on muzakki satisfaction at Baitul Mal, Aceh Tamiang Regency. From the results of the F test shows the results of F count 19,213 with a sig value of 0.000 <0.05, it means that service and trust together have a significant effect on muzakki satisfaction at Baitul Mal, Aceh Tamiang Regency. Limitations based on the R2 Test of 27% of service and trust affect the satisfaction of muzakki at Baitul Mal, Aceh Tamiang Regency, while 73% are explained by other factors not included in this study . Practical Implications – As a practical implication, the results of this study can be used as a reference by the government, especially zakat institutions in encouraging strategies to pay zakat, especially in terms of the cognitive domain, affective domain and psychomotor domain .